AI 2013: Advances in Artificial Intelligence 26th Australasian Joint Conference, Dunedin, New Zealand, December 1-6, 2013. Proceedings - Cranefield, Stephen; Nayak, Abhaya; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 26th Australasian Joint Conference on Artificial Intelligence, AI 2013, held in Dunedin, New Zealand, in December 2013. The 35 revised full papers and 19 revised short papers presented were carefully reviewed and selected from 120 submissions. The papers are organized in topical sections as agents; AI applications; cognitive modelling; computer vision; constraint satisfaction, search and optimisation; evolutionary computation; game playing; knowledge representation and reasoning; machine learning and data mining; natural language processing and information retrieval; planning and scheduling.
AI applications -- Cognitive modelling -- Computer vision -- Constraint satisfaction -- Search and optimisation -- Evolutionary computation -- Game playing -- Knowledge representation and reasoning -- Machine learning and data mining -- Natural language processing and information retrieval -- Planning and scheduling.
Keywords: Computer science; Computer software; Data mining; Information storage and retrieval systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl. Internet).; Computation by Abstract Devices; Information Storage and Retrieval; Data Mining and Knowledge Discovery